Non-invasive Portable Geophysical Tool to Monitor Water Content in Earthen Long Linear Infrastructures. (2017) - Utili, S.; Castellanza, R.; Galli, A.; Sentenac, P.
Abstract: The use of electrical conductivity measurements from a non-invasive hand held electromagnetic probe is showcased to monitor the water content of earthen embankments at routine inspections. A methodology to convert the electrical conductivity measurements from the electromagnetic device into water content values is illustrated. The methodology is based on measuring the soil electrical conductivity variation with respect to a baseline reference condition and calibrating a water content – electrical conductivity relationship by comparing electrical conductivity readings from the electromagnetic probes with water content readings taken from geotechnical probes installed in a few sections of the embankment. The values of water content converted from the conductivity measurements according to the proposed procedure were found to be in very good agreement with independent measures of water content taken at times well beyond the calibration period.